Effectiveness of Social Studies Teaching in Schools - Ghimire, Ram Kumar (Tribhuvan University Journal, 2013)
This study tries to explore the effectiveness of teaching of social studies at school level. The study tries to portray those criteria that are illustrated indifferent books by different writers. Findings have been drawn on the basis of the answers to the focused questions. Problems found in the field as perceived by the respondents are presented along with further areas of research. Social studies is the studies of human beings and human relation and the relation with environment. It is necessary to provide knowledge to the students about where they are living. It is becoming more important in the contemporary world. So, the policy makers and the stakeholders have to be serious to improve its teaching by finding suitable measures.